2022
DOI: 10.3390/biology11040522
|View full text |Cite
|
Sign up to set email alerts
|

Trophic Niche Breadth of Falconidae Species Predicts Biomic Specialisation but Not Range Size

Abstract: Trophic niche breadth plays a key role in biogeographic distribution patterns. Theory posits that generalist strategies are favoured in a more heterogeneous set of environments across a spatio-temporal gradient of resources predictability, conferring individuals and species a greater capacity for colonising new habitats and thus expanding their distribution area. Using the family Falconidae (Aves, Falconiformes) as a model study, we tested the prediction that those species with a wider diet spectrum will have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Specific environmental conditions might promote the development of physiological traits to cope with adverse conditions in different climatic regimes, although they might also require highly specialized functional features (Ghalambor et al, 2006;Bonetti & Wiens, 2014). Conversely, high versatility in relationship to resources and climatic conditions could, theoretically, enable a prominent capacity to colonize and occupy diverse habitat types (Jocque et al, 2010;Salisbury et al, 2012;Pigot & Tobias, 2013, 2015Lv et al, 2016;Fargallo et al, 2022). In many cases, palaeoclimatic changes might have promoted environmental flexibility by expanding climatic tolerance (Guerrero et al, 2013;Jara-Arancio et al, 2014;Ringelberg et al, 2020), a process that depends on the genetic variation of species populations (Somero, 2010;Pauls et al, 2013;Razgour et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Specific environmental conditions might promote the development of physiological traits to cope with adverse conditions in different climatic regimes, although they might also require highly specialized functional features (Ghalambor et al, 2006;Bonetti & Wiens, 2014). Conversely, high versatility in relationship to resources and climatic conditions could, theoretically, enable a prominent capacity to colonize and occupy diverse habitat types (Jocque et al, 2010;Salisbury et al, 2012;Pigot & Tobias, 2013, 2015Lv et al, 2016;Fargallo et al, 2022). In many cases, palaeoclimatic changes might have promoted environmental flexibility by expanding climatic tolerance (Guerrero et al, 2013;Jara-Arancio et al, 2014;Ringelberg et al, 2020), a process that depends on the genetic variation of species populations (Somero, 2010;Pauls et al, 2013;Razgour et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…5c and 5d). This reduces competition for migratory species and supports higher overall richness due to increased environmental heterogeneity (Fargallo et al, 2022) in TCan.…”
Section: Discussionmentioning
confidence: 59%
“…In our previous work, we have demonstrated the use of crowd-sourced bird diversity data in delineating the major ecoregions within a desert (Mukherjee et al, 2023). Such biogeographic distribution patterns in birds are known to be correlated to the trophic niche breadth (Fargallo et al, 2022). However, our further investigation on geographic distinctness of desert through mapping avian biodiversity with observational data, revealed that trophic niches not only play a crucial role in determining regional diversity but also the influx of migratory species (Mukherjee et al, 2024).…”
Section: Introductionmentioning
confidence: 99%